ARTIFICIAL INTELLIGENCE IN DIAGNOSTIC IMAGING: REVOLUTIONIZING HEALTHCARE DELIVERY - Dr. Carlos Fernández (Modern American Journals, 2025)
Artificial Intelligence (AI) is rapidly transforming the healthcare sector, particularly in the field of diagnostic imaging. AI-powered tools have shown immense potential in improving the accuracy, efficiency, and accessibility of diagnostic imaging, offering significant advancements in disease detection, interpretation, and patient care. This paper explores the role of AI in diagnostic imaging, with a focus on its applications in radiology, pathology, and other imaging modalities. It discusses AI algorithms' ability to assist healthcare providers in diagnosing complex conditions such as cancer, cardiovascular diseases, and neurological disorders. The paper also highlights the benefits of AI, including reduced diagnostic errors, improved workflow efficiency, and cost reduction. However, challenges such as data privacy concerns, the need for robust training datasets, and ethical considerations are also addressed. The paper concludes by discussing the future implications of AI in diagnostic imaging and the need for collaboration between clinicians, AI developers, and policymakers to ensure safe and effective implementation.
Keywords: Artificial Intelligence, diagnostic imaging, radiology, medical imaging, machine learning, deep learning, healthcare, diagnostic accuracy, healthcare delivery.